Groundwater Exploration through 2D Electrical Resistivity Tomography in Labi Agricultural Site, Belait District, Brunei Darussalam - Azffri, Siti; Gödeke, Stefan; Ahmad, Aziz; Ibrahim, Mohammad; Abdul Khalid, Amalina; Murphy, James Jasmir (Thai Geoscience Journal, 2022)
Over the years, Brunei has relied on surface water as the primary water source for domestic, industrial and agricultural use. Increasing population and demands for water, especially in its growing agriculture sector, has led to groundwater exploration at the Labi agricultural site for irrigation purposes driven by the Brunei Government. Electrical Resistivity Tomography (ERT) has been used extensively to delineate subsurface structures and groundwater prospects. The technique was employed in the study area using the pole-dipole array configuration with a survey line of 300 m and a target investigation depth of 100 m from the surface. The 2D resistivity model revealed groundwater zone with resistivity values ranging from 5 to 100 ohm-m. A borehole was drilled through this zone to a maximum depth of 80 m from the surface. A borehole drilling encountered multiple saturated layers of sand between depths of 4 to 78 m. Pumping test showed the groundwater was able to be produced at a steady rate of 288 m³/day. Aquifer transmissivity estimated using the unsteady Cooper Jacob analysis was 109 m²/day indicated moderate potential for groundwater usage in the study area for irrigation purposes. The resistivity survey, combined with borehole drilling and testing, provided insights into groundwater hydrology at the Labi agricultural site. The present study helped decision-makers take suitable measures to place future irrigation wells and achieve significant groundwater exploration results in the study area and other regions with similar geological settings.